2005
DOI: 10.1063/1.2079947
|View full text |Cite
|
Sign up to set email alerts
|

Density-functional calculations of relativistic spin-orbit effects on nuclear magnetic shielding in paramagnetic molecules

Abstract: Terms arising from the relativistic spin-orbit effect on both hyperfine and Zeeman interactions are introduced to density-functional theory calculation of nuclear magnetic shielding in paramagnetic molecules. The theory is a generalization of the former nonrelativistic formulation for doublet systems and is consistent to O(alpha4), the fourth power of the fine structure constant, for the spin-orbit terms. The new temperature-dependent terms arise from the deviation of the electronic g tensor from the free-elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(108 citation statements)
references
References 40 publications
3
103
2
Order By: Relevance
“…The results we have presented, which complement other studies, [18][19][20][22][23][24][25][26][27][28] show that DFT calculations should offer a major aid in understanding such spectra with minimal assumptions, for a wide variety of open-shell molecules. Indeed, we were able to show that some literature assignments can be easily corrected in this way.…”
Section: Discussionsupporting
confidence: 88%
“…The results we have presented, which complement other studies, [18][19][20][22][23][24][25][26][27][28] show that DFT calculations should offer a major aid in understanding such spectra with minimal assumptions, for a wide variety of open-shell molecules. Indeed, we were able to show that some literature assignments can be easily corrected in this way.…”
Section: Discussionsupporting
confidence: 88%
“…While the calculation of NMR properties of closed-shell, diamagnetic molecules is now widely used to aid structure determination [36][37][38][39]43], the corresponding computations for open-shell, paramagnetic species are comparatively less developed. Nevertheless, it has been shown that DFT methods can be used to predict NMR and EPR parameters for a variety of paramagnetic organic, organometallic and inorganic molecules [44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Density Functional Theory Calculations Of the Hyperfine Intementioning
confidence: 99%
“…Whereas the calculation of the NMR properties of diamagnetic molecules is widely applied [3][4][5][6][7], the corresponding computations for paramagnetic species are comparatively less developed. Nevertheless, it has been shown that DFT methods can be used to predict NMR and EPR parameters for a variety of paramagnetics [8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%